2019
DOI: 10.1001/jamanetworkopen.2019.3684
|View full text |Cite
|
Sign up to set email alerts
|

Association of Industry and Academic Sponsorship With Negative Phase 3 Oncology Trials and Reported Outcomes on Participant Survival

Abstract: Key Points Question Does an association exist between the sponsorship and conduct of phase 3 randomized clinical trials for cancer drugs despite negative or absent phase 2 trials for the drug, and does an association exist for overall patient survival and such phase 3 trials? Findings This analysis of 67 studies found that both industry and academia conducted negative phase 3 trials of cancer drugs. No association was found between trial sponsorship and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The average cost of an oncological phase III trial has been estimated to be up to $200 million. 44 , 45 Phase II data should be critically assessed about whether the phase III studies likely to be positive, potentially with some absolute thresholds based on data such as provide in our study. Ideally, drugs with clinically meaningful and statistically significant benefits are developed.…”
Section: Discussionmentioning
confidence: 99%
“…The average cost of an oncological phase III trial has been estimated to be up to $200 million. 44 , 45 Phase II data should be critically assessed about whether the phase III studies likely to be positive, potentially with some absolute thresholds based on data such as provide in our study. Ideally, drugs with clinically meaningful and statistically significant benefits are developed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, preclinical animal models serve as the foundation for clinical trials, but have exhibited suboptimal methods,38 which may explain why animal study results fail to successfully translate to clinical benefit. In fact, it was recently shown that many phase 3 trials in Oncology are conducted despite no significant phase 2 results 39. One possible explanation for why phase 3 trials proceed despite non-significant phase 2 results is the strong bioplausibility demonstrated in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, preclinical animal models serve as the foundation for clinical trials, but have exhibited suboptimal methods 36 , which may explain why animal study results fail to successfully translate to clinical benefit. In fact, it was recently shown that many phase 3 trials in Oncology are conducted despite no significant phase 2 results 37 . One possible explanation for why phase 3 trials proceed despite nonsignificant phase 2 results is the strong bioplausibility demonstrated in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%